Negotiation power and the impact of gender differences - Karin Zulauf; Ralf Wagner (Businesses, 2021)
This study focuses on the intersection of power and gender in negotiations, which is seldom challenged in previous research. In an experiment with 72 negotiators, we consider issue authority as a proxy of power in negotiations and investigate how different power allocations affect the negotiation success. We learn that an increase in issue authority for one of the two parties does not necessarily lead to an increase in success. Especially, female negotiators rely on their negotiation power, rather than systematically improving mutual utilities. This article contributes to Emerson's power-dependence theory, social role theory, role congruity theory, and gender role conflict theory by combining analyzing the impact of gender differences and power on the success. This study attempts to close the gap in the literature by focusing on the prospective function of gender role orientation in explaining gender differences in negotiation. The theoretical contribution is that females are not per se inferior in negotiations, but their performance decreases in scenarios of power asymmetries. On the contrary, unbalanced power decreases the likelihood of success. Negotiators cannot rely on a power advantage to increase their success.
Keywords: 650; negotiation power; formal negotiation procedure; gender; issue authority